Periode Kritis Kacang Hijau (Phaseolus aureus L.) Akibat Persaingan dengan Gulma dan Macam Pengolahan Tanah pada Tanah Mediteran Merah di Desa Socah Kecamatan Socah Bangkalan - Ainur Rafiq Amrullah; Sidqi Zaed Z.M; Slamet Supriyadi (Agrovigor, 2008)
Mung bean is one of leguminose plants planted in the third  order after soy bean and ground nut.  The presence of weeds on certain growth periode (critical periode) and at certain population can cause to reduce the yield of this plant.  This research aimed to study the critical periode of mung bean as the affected by the presence of weeds on different soil tillage.  The study was carried out on horticulture station research, Socah District, Bangkalan Regency with red mediteran (Alfisol) soil type. The research was arranged in a randomized block design with two factors. The first factor was the clear away weed consisted of  8 levels and the second factor was soil tillage method consisted two levels.  Result showed that there were significant interaction between the way in clearing away weeds and soil tillage treatment on the plant height, leaf area, leaf number, fresh and dry weight of plant, pod number, and dry weight of seed of plant.  Moreover,  the longer weeds present in assosiation with mung bean plant was the higher the effect of the weeds to reduce the yield. The higher yield was resulted from plant growing on the tilled soil. The critical periode of mung bean plant growing in the competition with weeds on untilled and tilled soil respectivelly was between 2 and 4 weeks after planting and between 6 and 8 weeks after planting.